Messenger RNA vaccine based on recombinant MS2 virus‐like particles against prostate cancer. Issue 7 (8th October 2013) - Li, Jinming; Sun, Yanli; Jia, Tingting; Zhang, Rui; Zhang, Kuo; Wang, Lunan
<x xml:space="preserve">Abstract</x> Prostate cancer (PCa) is the most diagnosed cancer in the western male population with high mortality. Recently, alternative approaches based on immunotherapy including mRNA vaccines for PCa have shown therapeutic promise. However, for mRNA vaccine, several disadvantages such as the instability of mRNA, the high cost of gold particles, the limited production scale for mRNA‐transfected dendritic cells in vitro, limit their development. Herein, recombinant bacteriophage MS2 virus‐like particles (VLPs), which based on the interaction of a 19‐nucleotide RNA aptamer and the coat protein of bacteriophage MS2, successfully addressed these questions, in which target mRNA was packaged by MS2 capsid. MS2 VLP‐based mRNA vaccines were easily prepared by recombinant protein technology, nontoxic and RNase‐resistant. We show the packaged mRNA was translated into protein as early as 12 hr after phagocytosed by macrophages. Moreover, MS2 VLP‐based mRNA vaccines induced strong humoral and cellular immune responses, especially antigen‐specific cytotoxic T‐lymphocyte (CTL) and balanced Th1/Th2 responses without upregulation of CD4+ regulatory T cells, and protected C57BL/6 mice against PCa completely. As a therapeutic vaccine, MS2 VLP‐based mRNA vaccines delayed tumor growth. Our results provide proof of concept on the efficacy and safety of MS2 VLP‐based mRNA vaccine, which provides a new delivery approach for mRNA vaccine and implies important clinical value for the prevention and therapy of PCa.